A BSA coated NOA81 PCR chip for gene amplification. Issue 12 (4th March 2016) - Qin, Kuiwei; Lv, Xuefei; Xing, Qiaorui; Li, Rui; Deng, Yulin
Abstract : We fabricated a NOA81 PCR chip (NP-chip) and first proposed a simple BSA coating method to successfully overcome the low PCR efficiency induced by the inhibition of the NP-chip which seriously impacted its application in the area of gene amplification. Abstract : Norland Optical Adhesive 81 (NOA81) is an excellent material for a microfluidic chip, but this chip has been rarely used in the field of gene amplification due to the inhibition effect on the polymerase chain reaction (PCR). In this study, a NOA81 PCR chip (NP-chip) was developed with a simple, fast fabrication method. To overcome this inhibition effect, a simple bovine serum albumin (BSA) coating method was introduced and the BSA coated pH and concentration were optimized for a better gene amplification effect. The PCR results of HLA-DRB1 indicated that the BSA coating method could greatly improve the PCR efficiency on the NP-chip. Moreover, two kinds of PCRs were performed on the NP-chip to validate the effectiveness of the BSA coating method. (i) Gene mutation of anti EB variable region gene (AEB-HC6-6) was observed under the conditions of cobalt radiation. (ii) Short Tandem Repeats (STRs) PCR was performed on the NP-chip as the multiple-primers PCR. The results showed that the NP-chip with BSA coating was able to successfully realize single and multiple primer gene amplification. With further improvement of the precise temperature control, this kind of NP-chip would be widely applied in gene amplification and promote the development of the miniature gene amplification device in point of care testing (PCOT), forensic detection, etc.